Assessment of water use, facilities, and practices towards water conservation and efficiency measures in UP Diliman - Abalos, Bernardino A. Jr; Tadeo, Monikka Mae L.
A comprehensive assessment may provide an overview of the present state of water use, facilities, and practices adapted in buildings in UP Diliman. It may also be used to pinpoint the probable sources of water wastage. This could be achieved through identification and review of implemented policies in the campus and comparing these with existing Water Management Plans of international universities. Survey tools were used to measure the willingness of the Building Administrators, students, and personnel in contributing to water conservation and efficiency efforts. A site inspection was conducted in order to document the current condition of water utilities. The existence of non-standardized water management programs, the need of maintenance and repairs of old water fixtures, and the lack of active participation of the community in promoting water conservation, are documented as some of the major causes of increasing water consumption in some building units. Nonetheless, an overall reduction in the annual water consumption for the past five years is concluded to be mainly due to the efficiency improvements of the water utilities. Thus, this should be continued together with other adaptive management strategies, such as those formulated in this study.